The Effect of a Proposed Instructional Program Based on the Multiple Intelligences Theory on EFL Jordanian Ninth-Grade Students' Achievement in English - Zeina Mohammad Al-Abdallat; Hamzah Ali Al-Omari (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: This study aimed to investigate the effect of a proposed instructional program based on Multiple Intelligences Theory (MIT) on ninth grade students' achievement in English. Methods: The participants of the study consisted of 40 students in two sections who were randomly assigned to a control group (20 students) and to an experimental group (20 students). One research instrument was used to collect the data of the study; a comprehensive English achievement test of reading, writing, listening and speaking. Data were analysed using means, standard deviations, ANCOVA and MANCOVA. Results: The findings of the study indicated that there was a statistically significant difference (α=0.05) between the mean score of the students of the experimental group who were taught according to the (MIT) program and that the mean score of the control group who were taught based on the conventional method. This difference was in favour of the experimental group students since the adjusted mean score was (55.20), which was higher than the adjusted mean score of the control group (46.45). Conclusions: The proposed instructional program based on (MIT) was significantly more effective than the conventional method in developing students' English language skills. The study recommends that (MIT) should be incorporated in English as a foreign language (EFL) curricula in Jordan to improve students' English language skills.